2014
DOI: 10.1177/1071100714558507
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crosslinking on the Wear Performance of Polyethylene Within Total Ankle Arthroplasty

Abstract: Highly crosslinked polyethylene may reduce clinical complications of total ankle replacement that are linked to polyethylene wear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…In contrast, Bischoff et al reported mean ECDs for CPE and HXLPE that were similar to those in the present study. 5 Macrophages are derived from monocytes, present at significantly higher concentrations in areas of osteolysis, and primarily responsible for bone loss in osteolytic lesions. 8 Exposure of implant wear particles to macrophages leads to release of inflammatory cytokines and the activation of the RANKL pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Bischoff et al reported mean ECDs for CPE and HXLPE that were similar to those in the present study. 5 Macrophages are derived from monocytes, present at significantly higher concentrations in areas of osteolysis, and primarily responsible for bone loss in osteolytic lesions. 8 Exposure of implant wear particles to macrophages leads to release of inflammatory cytokines and the activation of the RANKL pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the results of our study are consistent with the literature. 5,17,23 Finally, the true AP translation of the tibiotalar joint in the native ankle and in an ankle arthroplasty are Estimated standard deviation for the distribution. The standard deviation was not given in the paper; only the standard error was given.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marginal evidence from in vitro testing of HXPE indicates wear reduction when compared with non-CPE. 21 The cumulative annual failure rate in the UK for ankle replacements has been reported as being as low as 1.9% per annum. Five-year survivorship data from other national joint registries are: New Zealand: 93%; Sweden: 81%; Finland: 83%; Norway: 89% and 4-year survivorship in the Australian registry at 90%.…”
Section: Operative Managementmentioning
confidence: 99%
“…Wear and damage of polyethylene inserts in total joint arthroplasty (TJA) remain major factors that could lead to implant failure, potentially leading to implant loosening and revision in total ankle arthroplasty (TAA) . Contact mechanics at the metal–polyethylene articulation influence polyethylene wear .…”
mentioning
confidence: 99%